Decentralization and local government in the Caribbean - Cramer, Winston (National Democratic Institute for International Affairs GeorgetownGY, 2004)
Presents an analysis of the responses of the Country Survey Information Questionnaire used at the Decentralization and Local Government in the Caribbean Conference which was held in 2002. Includes two presentations made to the Joint Task Force on Local Government Reform, Guyana. Looks at issues such as human and financial resources capabilities; advantages and disadvantages of local government decentralization; local government decentralization and gender; and, fiscal decentralization.